Quality of Life Within the First 6 Months of Vestibular Schwannoma Diagnosis With Implications for Patient Counseling. Issue 10 (December 2018) - Carlson, Matthew L.; Tombers, Nicole M.; Kerezoudis, Panagiotis; Celda, Maria Peris; Lohse, Christine M.; Link, Michael J.
Abstract : Objective: To evaluate quality-of-life (QOL) in patients with sporadic vestibular schwannoma (VS) with particular focus on those recently diagnosed. Study Design: Cross-sectional survey, Penn Acoustic Neuroma Quality of Life (PANQOL) instrument. Setting: Acoustic Neuroma Association and a single tertiary referral center. Patients: Patients with sporadic VS. Main Outcome Measures: Domain-specific and total PANQOL scores comparing treatment modalities after adjusting for baseline covariates of interest. Results: Among all 1, 288 respondents there were 229 (18%) who were recently diagnosed and had not yet selected a treatment modality, 303 (24%) who were observed, 185 (14%) who underwent radiosurgery alone, 507 (39%) who underwent microsurgery alone, and 64 (5%) who underwent radiosurgery and microsurgery. After adjusting for covariates of interest, total PANQOL scores were highest for the observation cohort (65; 95% CI 62–68), lowest for patients treated with multimodality therapy (56; 51–61) and those recently diagnosed (58; 55–62), and intermediate for those who received microsurgery alone (60; 58–62) and radiosurgery alone (61; 57–64) (global comparison, p = 0.001). When comparing groups that received single-modality therapy, there were no statistically significant differences in total PANQOL scores at short (0–5 yr), intermediate (6–10 yr), or long-term (≥11 yr) follow-up after adjusting for baseline covariates (all, p > 0.05). Conclusion: A new diagnosis of VS frequently imparts significant anxiety on the patient and leads to a temporary reduction in QOL. Notably, anxiety domain QOL scores among patients with newly diagnosed VS are poorer than patients who have observed their tumor for 6 months or longer. When feasible, an initial period of observation may afford patients valuable time to reconcile with the new diagnosis, to learn more about treatment options, and to discover whether there is tumor growth. In turn, this valuable information can be used to inform sound decision-making regarding tumor management.